Computer Recognition Systems 2 - Kurzynski, Marek; Puchala, Edward; Wozniak, Michal; Zolnierek, Andrzej (Advances in Intelligent and Soft Computing,, 2007)
Computer recognition systems are nowadays one of the most promising directions in artificial intelligence. This book presents actual comprehensive study of this field. It contains a collection of over one hundred carefully selected articles contributed by experts of pattern recognition. It reports on current research with respect to both methodology and applications. In particular, it includes the following sections: Features, learning and classifiers, Image processing and computer vision, Speech and word recognition, Medical applications, Various applications. This book is a great reference tool for scientists who deal with the problems of designing computer pattern recognition systems. Its target readers can be the as well researchers as students of computer science, artificial intelligence or robotics.